Work Support and Resilience: Mediating Roles of Stress and Health Among Indonesian Gig Workers - Siregar, Ilhamsyah; Panjaitan, Nurhikmah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The gig economy in Indonesia has grown rapidly, but gig workers face significant challenges, including job stress and health issues that impact their resilience. This study examines how work support influences work resilience among gig workers in North Sumatra, focusing on the mediating roles of job stress, mental health, and physical health. The objective was to investigate the direct and indirect effects of work support on resilience in a culturally relevant context. A cross-sectional survey was conducted with 387 gig workers, including ride-hailing drivers, food delivery workers, and freelancers, using validated scales to measure work support, job stress, mental health, physical health, and resilience. Data were analyzed using structural equation modeling to test direct and mediating relationships. The findings show that work support directly enhances resilience and indirectly improves it by reducing job stress and improving mental and physical health. The model explains a significant portion of resilience variance, highlighting the critical role of support in mitigating gig work challenges. In conclusion, comprehensive support systems are essential for fostering resilience among gig workers, particularly in Indonesia, where cultural and platform-related factors shape worker well-being.